Vitamin C Fosters the In Vivo Differentiation of Peripheral CD4+ Foxp3− T Cells into CD4+ Foxp3+ Regulatory T Cells but Impairs Their Ability to Prolong Skin Allograft Survival - Oyarce, Karina; Campos-Mora, Mauricio; Gajardo-Carrasco, Tania; Pino-Lagos, Karina (Frontiers in Immunology, 2018)
Regulatory T cells (Tregs) are critical players of immunological tolerance due to their ability to suppress effector T cell function thereby preventing transplant rejection and autoimmune diseases. During allograft transplantation, increases of both Treg expansion and generation, as well as their stable function, are needed to ensure allograft acceptance; thus, efforts have been made to discover new molecules that enhance Treg-mediated tolerance and to uncover their mechanisms. Recently, vitamin C (VitC), known to regulate T cell maturation and dendritic cell- mediated T cell polarization, has gained attention as a relevant epigenetic remodeler able to enhance and stabilize the expression of the Treg master regulator gene Foxp3, positively affecting the generation of induced Tregs. In this study, we measured VitC transporter (SVCT2) expression in different immune cell populations, finding Tregs as one of the cell subset with the highest levels of SVCT2 expression. Unexpectedly, we found that VitC treatment reduces the ability of natural Tregs to suppress effector T cell proliferation in vitro, while having an enhancer effect on TGF-induced Foxp3+ Tregs. On the other hand, VitC increases induced Tregs generation in vitro and in vivo, however no allograft tolerance was achieved in animals orally treated with VitC. Lastly, Tregs isolated from the draining lymph nodes of VitC-treated and transplanted mice also showed impaired suppression capacity ex vivo. Our results indicate that VitC promotes the generation and expansion of Tregs, without exhibiting CD4+ T cell-mediated allograft tolerance. These observations highlight the relevance of the nutritional status of patients when immune regulation is needed.